1-D compressibility behaviour of cement-lime stabilized soft clays. Issue 7 (6th June 2020) - Wang, Dongxing; Korkiala-Tanttu, Leena
Abstract: This paper addresses the effect of chemical stabilisation on the one-dimensional compression behaviour of natural soft clay, based on incremental loading oedometer tests. The effect of cement-lime mixture with curing period from 1 to 28 days is evaluated for various dosages ranging from 1 to 13% by dry mass of clay. An important effect of cement-lime stabilisation is the development of cementation-induced yielding stress, associated with the initial void ratio, position and shape of compression curves as well as the ability of sustaining higher effective consolidation stress. The result provides the effect of cement-lime treatment on the compression index, coefficient of consolidation and hydraulic conductivity. The role played by cement-lime dosage is investigated in the evolution of compression index, creep coefficient and ratio of compression index to creep coefficient. The time-dependency of creep coefficient is studied on stabilised clays with various cement-lime dosages. The compression results are complemented by the stress-dependent analysis of creep coefficient and compression modulus, which provides insight into the influence of effective stress levels on treated clays with different dosages of cement-lime. This study provides a reference to analyse the effect of cement-lime stabilisation on natural soft clays in the practice of soft ground improvement.